Kesiapan CHSE di Era New Normal (Studi Kasus: Airbnb di Kota Denpasar, Bali) - Aritenang, Adiwan F.; Setiawan, Shafa Kamila Putri (Centre For Tourism Planning and Development, 2024)
This research examines Airbnb listings’ readiness to fulfils CHSE in Denpasar City. This result shows three priority amenities: a fire extinguisher, a first aid kit, and a smoke detector. However, the readiness of Airbnb to meet CHSE requirements remains limited and only found in certain types of listing. The study provide important insights into the lack of CHSE implementation among Airbnb listings, mainly in private and hotel room listings. This problem is further exacerbated by the difficulty of supervising the implementation of the CHSE, as Airbnb’s legal status remains debatable following hosts’ willingness to register with the Tourism Office.